Antimicrobial Resistance Profile and Biofilm Production of Microorganisms Isolated from Oropharynx of Rupornis magnirostris (Gmelin, 1788) and Caracara plancus (Miller, 1777) - Fernanda Alda da Silva; Sandrelli Meridiana de Fátima Ramos dos Santos Medeiros; Sérgio Dias da Costa-Junior; Ana Emília Medeiros Roberto; Sarah Brandão Palácio; Reginaldo Gonçalves de Lima-Neto; Rejane Pereira Neves; Carolina Peixoto Magalhães; José Eduardo Garcia; Isabella Macário Ferro Cavalcanti (Veterinary Medicine International)
The aim of this preliminary study was to identify microorganisms with antimicrobial resistance profile and biofilm producers in oropharynx of Rupornis magnirostris and Caracara plancus. Six R. magnirostris and six C. plancus maintained in Triage Center for Wild Animals (CETAS) facilities were studied. Coagulase-positive staphylococci (CoPS), enterobacteria, and yeasts were identified by the biochemical analysis or MALDI-TOF mass spectrometry. The resistance profile of the microorganisms was analyzed according to CLSI. The biofilm production was evaluated by Congo red and violet crystal staining methods. Among the 12 birds, 10 presented strains of CoPS and/or enterobacteria with resistance profile, such as methicillin-resistant CoPS (MR-CoPS), vancomycin-resistant CoPS (VR-CoPS), extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL), and Klebsiella pneumoniae carbapenemase- (KPC-) producing bacteria. Regards the fungal analysis, Candida spp., Cryptococcus spp., Rhodotorula mucilaginosa, R. glutinis, and Trichosporon coremiiforme were identified. All the Trichosporon coremiiforme strains were resistant to amphotericin B, as well as all the Rhodotorula mucilaginosa exhibited resistance to fluconazole. Related to the biofilm production, among the 8 CoPS, 27 enterobacteria, and 10 yeasts isolates, 3, 16, and 7 strains were biofilm producers, respectively. Thus, the presence of these microorganisms in birds of prey is worrisome, highlighting its possible influence in the spread of infections in urban centers.